Knowledge Relationships on Covid-19 Preventive Actions - Puguh Santoso; Novita Setyowati (Universitas Muhammadiyah Semarang, 2020)
Disease caused by the corona virus, otherwise known as COVID-19, is a new breed that was discovered in 2019 and has never been identified as attacking humans before. The corona virus can easily spread and infect anyone regardless of age. This virus can be transmitted easily through contact with sufferers. Health quarantine is the limitation of activities and / or separation of a person who is exposed to an infectious disease as stipulated in laws and regulations even though he has not shown any symptoms to prevent the possibility of spreading to people around him. Preventive action activities require knowledge in order to educate the public in making decisions for preventive action. The purpose of this study was to determine the relationship between knowledge and prevention measures for Covid-19. This research is a quantitative study, with a correlation analytic design. Data were analyzed with spearment correlation. The sample used in this study were residents of RW 07, Pesantren Kota Kediri, who were taken randomly through the google form application which was distributed through the WhatsApp group. The number of samples taken was 90 respondents. The results of statistical tests, it was found that the p value was 0.001, which means that the p value was less than alpha (P <0.05), which means that Ho was rejected, so it can be concluded that there is a relationship between knowledge of Covid-19 prevention measures.